MENUJU DESA INKLUSIF: PERENCANAAN PEMBANGUNAN BERKELANJUTAN UNTUK DESA ADAT NEGERI HUKURILLA DI KOTA AMBON: PERENCANAAN PEMBANGUNAN BERKELANJUTAN UNTUK DESA ADAT NEGERI HUKURILLA DI KOTA AMBON - Manuputty, Feky; Loppies, Lussi R.; Afdhal, Afdhal; Litaay, Simona Ch. H. (CV. Kalimasada Group, 2023)
Social exclusion in the form of discrimination and intolerance has reached remote villages, including Hukurila Village, South Leitimur District, Ambon City. This act of exclusion occurred due to the low understanding of social change agencies in the village in terms of implementation and dynamics of planning inclusive village development programs. Apart from that, the amount of human resources and skills they have in the implementation and dynamics of planning inclusive village development programs is also relatively low. Due to this problem, strategic steps are needed in building inclusive villages with comprehensive training activities for change agents in Hukurila Village, South Leitimur District, Ambon City. Training and mentoring methods for development agents is one solution to overcome this problem. The activity program was implemented involving village government officials, community leaders, traditional leaders, religious leaders, youth leaders and women's leaders, as well as change agent groups in Hukurila Village, South Leitimur District, Ambon City. The result of this activity is an increase in the number of human resources, knowledge and skills of partners in implementing inclusive village development program planning in Hukurila Village, South Leitimur District, Ambon City.